2021
DOI: 10.1097/qai.0000000000002640
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sexual Behavior, PrEP Adherence, and Access to Sexual Health Services Because of the COVID-19 Pandemic Among a Cohort of PrEP-Using MSM in the South

Abstract: Individual and in-training subscription rates include print and access to the online version. Institutional rates are for print only; online subscriptions are available via Ovid. Institutions can choose to purchase a print and online subscription together for a discounted rate. Institutions that wish to purchase a print subscription, please contact Wolters

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 21 publications
13
89
1
2
Order By: Relevance
“…Our results differ from other studies that evaluated STD prevalence using the same methodology as ours [ 4 , 5 ]. In our case, we did not observe a significant reduction in cases of urethritis in our health region in spite of strict lockdown from mid-March to the end of May, probably due to the ease of access to emergency services.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ from other studies that evaluated STD prevalence using the same methodology as ours [ 4 , 5 ]. In our case, we did not observe a significant reduction in cases of urethritis in our health region in spite of strict lockdown from mid-March to the end of May, probably due to the ease of access to emergency services.…”
Section: Discussioncontrasting
confidence: 99%
“…However, another study [4] in Cuba showed that cases of syphilis and gonorrhea decreased significantly during the period of social restrictions imposed due to the first wave of COVID-19. Events were similar in other countries [5].…”
Section: Introductionsupporting
confidence: 74%
“…23,24 Early research suggests that initiation of social distancing measures changed the patterns of PrEP use, and although some individuals chose to cease PrEP owing to changes in sexual behavior, others experienced difficulties in accessing testing and monitoring services. 25 This evaluation shares the barriers to PrEP access in PH-partnered telehealth programs during a PH crisis but also highlights the strategies used by an integrated program to continue CTR and PrEP services delivery.…”
Section: Discussionmentioning
confidence: 96%
“… 12 , 14 Emerging evidence in Oregon, California, and Georgia is also consistent with the declines in STD reporting observed in this report. 15 - 17 Some researchers have documented starker declines in STD testing among asymptomatic clients when compared to symptomatic cases. 18 The findings in this study are consistent with this notion given the largest decrease in STD reporting was observed among chlamydial cases, which are largely detected through routine screenings.…”
Section: Discussionmentioning
confidence: 99%